Effectiveness of Domperidone in Augmenting Breastmilk Production Measured by Manual Expression in Postpartum Women in Charoenkrung Pracharak Hospital - Maneenin Wannapat (2022)
Background: Breastmilk is the ideal food for infants. Domperidone was found to increase breastmilk production but its use is still controversial. Most of the studies used electric breast pump to collect breastmilk. However, manual expression of breastmilk has some advantages over electric breast pump. Objective: To study effectiveness of domperidone in increasing breastmilk production among postpartum women by using manual expression to collect breastmilk. Methods: This study recruited 50 postpartum women who had term spontaneous normal vaginal delivery in Charoenkrung Pracharak Hospital from September 1, 2015 to November 30, 2015. The participants were randomly assigned to receive domperidone or placebo, 25 women in each group. Drugs were first given to postpartum women at 24 hours after delivery. Breastmilk was collected by manually expression at 24 hours after delivery before receiving drugs, then at 48 hours, 72 hours and 96 hours after delivery. Chi-Square test and Mann-Whitney U test were used for hypothesis testing and the statistical significance was set at P < 0.05. Results: The median volume of breastmilk in both groups at 24 hours after delivery and before receiving drugs were 2 milliliters in domperidone group and 1 milliliter in placebo group. Breastmilk median volume increased in both groups afterwards. At 48 hours after delivery, the volumes were 8 and 3 milliliters in domperidone and placebo group respectively. At 72 hours, the volumes were 15 and 10 milliliters, at 96 hours, the volumes were 35 and 15 milliliters in groups respectively. The differences were statistically significant (P < 0.05). There was no side effect of domperidone among the postpartum women in the domperidone group. Conclusion: Domperidone effectively increased more breastmilk production measured by manual expression than placebo.